Cross-Country Variations in Aggregate Volatility: Evidence from 56 Countries - Allen C. Head (Queen's University, Department of Economics, 1991)
Relationships between country size (measured by both population and aggregate GDP) and standard of living (measured by per capita GDP) and the volatilities of aggregate output, consumption, and investment are investigated for a sample of 56 countries. Both characteristics are shown to be negatively related to the volatilities of the growth rates of all three aggregate for the period 1950-85. The relationships between the importance of nontradable goods (measured by the ratio of consumption expenditures on nontradables to expenditures on tradables) and the volatilities of aggregates are studied for a sub-sample of 23 countries. This characteristic and volatilities of all three aggregates are shown to be negatively related. These results are consistent with the predictions of theoretical models studied by Crucini (1990) and Head (1991).
Keywords: 330